Understanding Teachers’ Motivation and Barriers in Implementing Balanced Nutrition Guidelines in Indonesia: A Self-Determination Theory Perspective - Nurzakiah Nurzakiah; Nurhaedar Jafar; Ridwan M. Thaha; Veni Hadju (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Non-communicable diseases (NCDs) are currently the leading cause of morbidity and mortality worldwide, including in Indonesia. The Indonesian government promotes balanced nutrition guidelines to encourage healthy lifestyles, with teachers expected to model these behaviors. This study is grounded in Self-Determination Theory (SDT), which posits that motivation, autonomy, competence, and relatedness influence health behaviors. It aims to explore teachers’ practices and perceived barriers in implementing balanced nutrition guidelines. Methods: A qualitative study using Focus Group Discussion (FGD) was conducted involving 11 teachers from a public school in Makassar City, Indonesia. The discussion was guided by a set of structured questions developed based on the 10 key messages of the Indonesian balanced nutrition guidelines. The FGD explored daily dietary practices, physical activity, and perceived barriers to the adoption of balanced nutrition recommendations. Results: The study involved 11 teachers from a public senior high school in Makassar City, Indonesia, most of whom were female and over 40 years old. The findings showed that teachers implemented the guidelines only partially. Practices included consuming vegetables only once a day, preparing simple side dishes such as fish or tempeh, consuming rice as the main and often sole staple food, inadequate water consumption, and performing only light or incidental physical activity. Several barriers were identified, including limited time for food preparation due to work demands, lack of breakfast habits, fear of frequent urination due to increased water intake, and limited time or motivation to engage in physical activity. Teachers also expressed that health behaviors were not yet a priority in their daily routines. These behaviors were interpreted through SDT constructs, highlighting how unmet psychological needs hinder full adoption of balance nutrition guidelines. Conclusion: The study highlights that while teachers are aware of balanced nutrition guidelines, their implementation remains limited due to various time, behavioral, and motivational barriers. Interventions based on SDT that promote autonomy, competence, and social support may enhance the adoption of balanced nutrition practices among teachers.